Foreign Languages Teachers’ Beliefs in Infusing Moral Values in Their Teaching Practices - Nirwanto, Rahmadi; Rahmah, Yulia; Dewi, Binar Febriyanti; Airlangga, M. Irsyad (Universitas Pahlawan Tuanku Tambusai, 2024)
Teachers’ beliefs play a fundamental role in building the foundation for the teachers’ classroom practices. Beliefs determine what they say and do. The present study investigates teachers’ beliefs related to infusing moral values in their teaching practices. The data were collected through interview with six foreign language teachers (three Arabic teachers and three English teachers) who participated in the study. Finding indicated that the teachers hold a variety of beliefs about; a) the moral values, b) the ways they used to nurture moral values, and c) the factors that influence the instillation of moral values. The findings suggest that future researchers could deploy methods such as observation, document analysis, and other methods to provide a more comprehensive understanding and depiction of how moral values are viewed and integrated by foreign languages teachers.